(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Dilated cardiomyopathy (DCM) in children remains one of the most challenging and devastating pediatric cardiac conditions, with implications ranging from chronic disability to death. The disorder is characterized by the dilation and impaired contraction of one or both ventricles, ultimately leading to systolic dysfunction and congestive heart failure. Understanding its multifactorial etiology has been an intense focus of pediatric cardiology, and among the many contributors to the disease, the immune system — both innate and adaptive — has emerged as a crucial determinant in its onset and progression. Delineating how the two pillars of immunity interact, escalate, or fail to control the pathological process is essential to designing effective diagnostics and therapeutic interventions.